Reassessing Hifdz Al-Nasl in the Age of Assisted Reproduction: a Maqashid Al-Shari’ah Perspective on Donor Artificial Insemination - Nasiri Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
The rapid advancement of Assisted Reproductive Technology (ART), specifically donor artificial insemination, has challenged the traditional boundaries of Islamic family law and bioethics. This research explores the relevance and repositioning of the concept of Hifdz al-Nasl (preservation of lineage) within the framework of Maqashid al-Shari’ah (the higher objectives of Islamic law). Using a qualitative normative-philosophical approach, this study evaluates classical jurisprudence prohibiting third-party genetic intervention against the modern context of genetic certainty and DNA technology. The findings indicate that the traditional "harm" (mafsadah) of lineage confusion, which serves as the primary basis for prohibition, is becoming increasingly mitigable through forensic registries and transparent bio-data systems. The study concludes that Hifdz al-Nasl should evolve from a strictly prohibitive tool into a protective mechanism for the child's identity and legal rights. By adopting a "Systemic Maqashid" approach, the research suggests that a highly regulated, non-anonymous donor system can satisfy the divine intent of protecting the family unit while fulfilling the human need for progeny. This study provides a theological-philosophical framework for harmonizing Islamic legal values with contemporary medical ethics.